Diversity and antibacterial and antioxidant activities of fungal endophytes from the roots of Eucalyptus deglupta - Wang, Wei; Mao, Ziling; Wu, Chunyin; Hamza Shahid,; Wang, Shengkun; Shan, Tijiang (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this study, 45 endophytic fungal strains were isolated from the roots of Eucalyptus deglupta. Among them, 16 distinct strains were identified and classified into 14 different genera (Celoporthe, Aspergillus, Castanediella, Chaetomium, Biscogniauxia, Sordariales, Pestalotiopsis, Clitopilus, Cylindrocladiella, Calonectria, Trichoderma, Xylaria, Neofusicoccum and Pleosporales) according to their morphological characteristics and molecular information. The genera Aspergillus and Calonectria were the dominant endophytic fungi in the roots of E. deglupta. In addition, the antibacterial and antioxidant activities of the 16 endophytic fungi isolated from the roots of E. deglupta were evaluated. All the strains displayed inhibitory activities against Agrobacterium tumefaciens, Bacillus subtilis, Escherichia coli, and Xanthomonas vesicatoria. Strains Edf-1 to Edf-4, Edf-11 and Edf-12 demonstrated strong inhibitory activity against R. solanacearum with plaque diameters between 5 and 10 mm. The crude extract of Edf-14 had inhibitory activity against all tested bacteria. Five strains, Edf-1 to Edf-5, demonstrated a strong scavenging capacity for 2,2-diphenyl-1-picrylhydrazyl (DPPH), with IC50 values of 0.26 ± 0.04, 0.11 ± 0.03, 0.20 ± 0.05, 0.10 ± 0.04 and 0.14 ± 0.02 mg/mL, respectively. Hence, endophytic fungi isolated from the roots of E. deglupta showed antibacterial and antioxidant activities, providing a theoretical foundation for further isolation and identification of specific active components.